Advancement in Paediatric Laparoscopic Surgery: Two Years’ Experience in A Tertiary Level Medical College Hospital in Bangladesh (Journal of Paediatric Surgeons of Bangladesh, 2025)
Introduction: Laparoscopic surgery has evolved rapidly in recent years and is considered a standard procedure in Paediatric surgery1. Recent advanced in the paediatric laparoscopy have largely concentrated on reducing the size of incisions needed to operate2. Now a days an increasing number of diagnostic and therapeutic surgical procedures are being done laparoscopically3. Methods: This retrospective paediatric laparoscopic study was carried in Dhaka Medical College and Hospital over a period of 2 years from Jan 2023 to Dec 2024. For different surgical conditions, age ranged 2 months to 12 years were operated laparoscopically for different surgical conditions. Results: A total 264 patients were operated laparoscopically. Out of them laparoscopic hernia repair was done on 85 patients, followed by laparoscopic appendectomy was in 59 patients, laparoscopic orchiopexy was in 51 patients, laparoscopic cholecystectomy was in 24 patients, laparoscopic assisted pull through was in 11 patients, diagnostic laparoscopy was in 10 patients, laparoscopic assisted ano rectoplasty was in 07 patients, laparoscopic pyeloplasty was in 03 patients, laparoscopic ovarian cystectomy was in 03 patients, laparoscopic excision of prostatic utricle was in 03 patients, others procedures was in 8 patients. Conclusion: Laparoscopic surgery is becoming the standard of care for many paediatric conditions. There is an increased demand from referring physicians as well as the public for laparoscopic surgery. Careful preparation and training are the cornerstones of successful outcome.Journal of Paediatric Surgeons of Bangladesh (2021) Vol. 12 (1 & 2):24-29